It gives me anxiety! Black Academics’ experiences of teaching large classes during the Covid-19 pandemic in a South African university - Mlamuli Nkosingphile Hlatshwayo; Thabile Zondi; Thabang Mokoena (Perspectives in Education, 2023)
The COVID-19 pandemic continues to disrupt the teaching and learning in international higher education. Those of us in the global South have particularly been hard hit, struggling to balance working/ functioning economies, a struggling healthcare system, education, commerce, trade, transport, and the community spread of what was later found to be a very infectious disease (Porter et al., 2021; Rogerson & Rogerson, 2020; Shamasunder et al., 2020). In this paper, we explored and theorised the experiences of academics who taught large classes at a research-intensive university in South Africa. We purposely recruited and interviewed eight academics for this case study. We drew on Chela Sandoval’s (2013) philosophical notion of “decolonial love” to theorise what an inclusive, democratic and ubuntu-orientated teaching of large classes could look like for us in the global South, beyond the pandemic. The findings revealed that academics continue to be frustrated/challenged/made anxious with teaching large classes due to inadequate infrastructure (digital), lack of resources, and general unpreparedness with the virtual/online teaching and learning. The findings also revealed that large classes were problematic as academics struggled to provide critical engagements and discussions during the hard Covid-19 lockdown, and with some lamenting the frustrations of “teaching to themselves” due to the lack of student engagement. We conclude this paper by proposing a decolonial love approach to the online teaching and learning of large classes, underpinned by the ethics of care, compassion and understanding in curriculum imaginations.